PENGARUH PEMBELAJARAN DARING TERHADAP PRESTASI BELAJAR SISWA DENGAN DUKUNGAN ORANG TUA SEBAGAI VARIABEL MODERASI PADA MADRASAH TSANAWIAH NEGERI 3 KOTA TIDORE KEPULAUAN - Jamaludin Sehat; Said Hasan; Marwan Man Soleman (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Education in Indonesia is currently still in the developing stage so it is necessary to improve the quality of education so that the Indonesian nation can develop in a better direction. So improving the quality of learning at a level of education is very important in order to give birth to the next generation who excel. An effective learning process will make student achievement more meaningful and meaningful. However, students in the online learning process get high scores but when tested at school there is a decrease in student achievement scores. So there are several factors that can affect student achievement including online learning, learning motivation and parental support. The purpose of this study is to determine the impact of learning achievement from these factors. The research method used is a quantitative descriptive approach with a research model using Moderate Regression Analysis (MRA). The results show that online learning has no significant effect on student achievement, parental support has a negative and significant effect on student achievement in MTs and the third hypothesis with parental support as a moderating variable is able to strengthen which results in a positive effect of online learning on student achievement in MTs. . Negeri 3 Tidore City of Tidore Islands. For parents and guardians of students to pay attention to providing support to students. The support provided must still pay attention to the independence of students in doing each task given by the teacher.